Peningkatan Kemampuan Menulis Paragraf Argumentasi melalui Metode Pembelajaran Siswa di Kelas X Madrasyah Aliyah Alkhairat Siniu - Abidin, Fardhi H (Bahasantodea, 2016)
Writing learning in the school of Madrasah Aliyah alkhairat Siniu need to get care of the teacher at the indonesian language subject. when the students faced at the writing learning of argumentation paragraph, the students always gets difficult. Along learning of writing, the students have less to care rules which have been in the writing skills. It was caused the students have weakness in writing skills of the students in writing argumentation paraghraph. The objective of tis research to (I) describe the students ability in writing argumentatin paraghraph at the tenth grade students of Madrasah Aliyah alkhairat Siniu using inquiry learning method. And (2) describe the result in improvement of students ability in writing argumentation paragraph at the tenth grade tudents of Madrasah Aliyah alkhairat Siniu using inquiry learning method. The method of this research which used in this reserch is descriptive method, that is a research method which try to decide which present be ready based on the datas. The design or model of this research is a classroom action research, that is Kemmis model. Which consist of (1) Planning, (2) Action, (3) observation, and (4) reflection. Based on the result of reseacrh at he cycle (I), it was about ability of the teacher (researcher) in doing a process of learning at the cycle I in the tenth grade students of Madrasah Aliyah alkhairat Siniu still in the minus category with the result presented 22,57%. At the cycle (II)the resut of teacher ability in doing learning process at the tenth grade students of Madrasah Aliyah alkhairat Siniu can be seen i the very good categorywith the result of prsented 34,08%. Finally, it can be concluded that learning the students with using inquiry strategy can improve students ability in writing argumentation paraghraph at the tenth grade students of Madrasah Aliyah alkhairat Siniu